2020
DOI: 10.1177/1533033820977524
|View full text |Cite
|
Sign up to set email alerts
|

MFAP2 Promotes the Proliferation of Cancer Cells and Is Associated With a Poor Prognosis in Hepatocellular Carcinoma

Abstract: Backgrounds: Microfibril-associated protein 2 (MFAP2) is an extracellular matrix protein that regulates the function of microfibrils by interacting with fibrillin. MFAP2 has been reported to play an important role in metabolic diseases and has been shown to be significantly overexpressed in head and neck squamous cell carcinoma and Hepatocellular carcinoma (HCC). However, the molecular function and prognostic value of MFAP2 have never been reported in HCC or other tumors. Methods: In the present study, express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…However, disease-induced fibrillin mutations may alter the ability of myofibrils to bind MFAP2, and lead to the occurrence and deterioration of the disease. Although some reports have described MFAP2 upregulation in HCC ( 14 ), its exact role therein remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, disease-induced fibrillin mutations may alter the ability of myofibrils to bind MFAP2, and lead to the occurrence and deterioration of the disease. Although some reports have described MFAP2 upregulation in HCC ( 14 ), its exact role therein remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, MFAP2 is upregulated in breast cancer ( 8 ), thyroid cancer ( 9 ), melanoma ( 10 ), ovarian cancer ( 11 ) and gastric cancer ( 12 , 13 ), and associated with the occurrence and progression of these tumors. Previous studies have also shown that MFAP2 is upregulated in HCC ( 14 ), but its role in the occurrence and development of the disease is unclear. In order to investigate the role of MFAP2 in the occurrence and development of HCC, the aim of the present study was to evaluate the expression of MFAP2 in liver cancer by analyzing the tumor specimens and detailed clinical data of 94 patients.…”
Section: Introductionmentioning
confidence: 99%
“…NNMT upregulation was already reported in oral squamous cell carcinoma [ 75 ], but its downregulation was associated with increased sensitivity to 5-fluorouracil in esophageal squamous cell carcinoma cells [ 76 ]. In contrast, MFAP2 upregulation was reported in head and neck cancer [ 77 ] and associated with poor prognosis in gastric and hepatocellular carcinomas [ 78 , 79 ]. Therefore, the downregulation of these genes in HPV-positive relative to HPV-negative OPSCC may contribute to the better prognosis and response to therapy observed in the first group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have described dysregulated MAGP-1 levels in diverse cancers underlining its implication in tumour progression, particularly in the processes of epithelial mesenchymal transition (EMT) due to its interaction with TGF-β [27]. In this sense, opposite gene expression levels of MFAP2 have been described in different tumour types as being upregulated in gastric [25], thyroid [33] and hepatocellular [34] carcinomas and downregulated in prostate carcinoma and paragangliomas [35].…”
Section: Discussionmentioning
confidence: 99%